Sustainable Increasing Market Share For Small To Medium Industrial Clusters - Suranto Suranto; Kurnia Nabila; Munajat Tri Nugroho; Ahmad Kholid Alghofari (Jurnal Info Sains : Informatika dan Sains, 2023)
Digital transformation is able to expand marketing in the context of business development to increase market share for small and medium industries (IKM). The aim of this research is business development to increase market share in SMEs. The benefits of research include input into effective marketing strategies in batik SMEs. Data collection methods through questionnaires, interviews, observation, literature study and documentation. The research object at batik SMEs centers involves business owners and consumers of batik products. The analytical method uses structural models to identify and analyze the relationship between exogenous and endogenous variables. Based on the research results, the model formulation applied is able to increase market share.